Uncovering the Cyclic AMP Signaling Pathway of the Protozoan Parasite Entamoeba histolytica and Understanding Its Role in Phagocytosis - Agarwal, Shalini; Rath, Pragyan Parimita; Anand, Gaurav; Gourinath, Samudrala (Frontiers in Cellular and Infection Microbiology, 2020)
Second messenger signaling controls a surprisingly diverse range of processes in several eukaryotic pathogens. Molecular machinery and pathways involving these messengers thus holds tremendous opportunities for therapeutic interventions. Relative to Ca2+ signaling, the knowledge of a crucial second messenger cyclic AMP (cAMP) and its signaling pathway is very scant in the intestinal parasite Entamoeba histolytica. In the current study, mining the available genomic resources, we have for the first time identified the cAMP signal transduction pathway of E. histolytica. Three heptahelical proteins with variable G protein coupled receptors domain, heterotrimeric G proteins (G, G and G subunits), soluble adenylyl cyclase, cyclase associated protein and enzyme carbonic anhydrase were identified in its genome. We could also identify several putative candidate genes for cAMP downstream effectors such as Protein Kinase A, A-kinase anchoring proteins and Exchange protein directly activated by cAMP pathway. Using specific inhibitors against key identified targets, we could observe changes in the intracellular cAMP levels as well as defect in the rate of phagocytosis of Red Blood Cells by the parasite E. histolytica. We thus, strongly believe that characterization of some of these unexplored crucial signaling determinants will provide a paradigm shift in understanding the pathogenicity of this organism.